Effects of apple cider vinegar on glycemic control and insulin sensitivity in patients with type 2 diabetes: A GRADE-assessed systematic review and dose–response meta-analysis of controlled clinical trials - Donya Arjmandfard; Mehrdad Behzadi; Zahra Sohrabi; Mohsen Mohammadi Sartang (Frontiers in Nutrition)
Background and aimsDiabetes mellitus (DM) is a multifactorial metabolic disorder that affects the body’s ability to regulate blood sugar levels. Apple cider vinegar (ACV) could possibly improve diabetes; nevertheless, evidences provide conflicting results. This study aimed to evaluate the effects of ACV on glycemic profile in type 2 diabetes patients (T2DM) in controlled trials (CTs) by systematically reviewing and dose–response meta-analysis.MethodsThe Scopus, PubMed, and Web of Science databases were searched until November 2024 according to a systematic approach. All CTs investigating ACV’s effects on glycemic factors were included. We used a random-effects model to calculate WMDs and 95% confidence intervals (CIs). The present study assessed publication bias, sensitivity analysis, meta-regression, and heterogeneity based on standard methods. We assessed the bias risk of the included studies using Cochrane quality assessments and used GRADE (Grading of Recommendations Assessment, Development, and Evaluation) to calculate evidence certainty. We registered the study protocol at Prospero (no. CRD42023457493).ResultsOverall, we included seven studies in this meta-analysis. ACV significantly reduced fasting blood sugar (FBS) (WMD: −21.929 mg/dL, 95% CI: −29.19, −14.67, p < 0.001) and HbA1c (WMD: −1.53, 95% CI: −2.65, −0.41, p = 0.008) and increased insulin (WMD: 2.059 μu/ml, 95% CI: 0.26, 3.86, p = 0.025), while it did not affect hemostatic model assessment for insulin resistance (HOMA-IR). We observed linear and non-linear associations between ACV consumption and FBS levels (p < 0.001). Each 1 mL/day increase in ACV consumption was associated with a-1.255 mg/dL reduction in FBS. Moreover, greater effects on FBS were in dosages >10.ConclusionACV had positive effects on FBS and HbA1c in T2DM patients.Systematic Review RegistrationThe study protocol was registered at Prospero (no. CRD42023457493).